Dental caries experience in relation to salivary findings and molecular identification of S. mutans and S. sobrinus in subjects with Down syndrome - de Castilho, Aline Rogéria Freire; Pardi, Vanessa; Pereira, Cássio Vicente (Odontology, 2011)
This study investigated the association between clinical and salivary or molecular parameters in Down syndrome subjects. Sixty individuals (1- to 48-year old) were clinically examined using DMFT/DMFS. Stimulated saliva was collected; salivary flow was calculated (mL/min), buffering capacity was measured using a standard pH tape. In addition, 25 μL of saliva was diluted using 10-fold-dilution method and then placed on Mitis-Salivarius-Bacitracin agar to count colony forming units (CFU/mL) of mutans streptococci. Polymerase chain reaction analysis identified species. Caries indexes were 0.65–13.5 (DMFT) and 0.65–26.0 (DMFS) according to groups. Ninety-four percent of subjects had low flow rate (0.7–1.0 mL/min) and 44% had low buffering capacity (pH < 4). Besides, 60% had more than 1 × 10 6 CFU/mL, 60% had S. mutans , and 41.4% had S. sobrinus . Caries indexes did not significantly correlate with flow rate, buffering capacity, CFU/mL by Pearson’s correlation ( p > 0.05), and showed no significant association with prevalence of species by Chi-square ( p > 0.05). There is no association between clinical picture and salivary or molecular parameters in Down syndrome subjects.